Viabilitas dan Vigor Benih Kedelai (Glycine max L.) pada Media Matriconditioning Berbahan Organik dan Anorganik - Sudirman Numba; Netty Syam; Jabal Rahmat Ashar; Fatmawati (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2024)
The availability of quality seeds affects the quality and production of soybeans produced. Seed quality often deteriorates due to prolonged storage, thus requiring in-vigoration treatment. The study aimed to determine the effect of organic matriconditioning media and inorganic matriconditioning media on improving the viability and vigor of soybean seeds. The research took place from September to December 2023. The research was organized using a completely randomized design with 5 treatments, consisting of 3 (three) matriconditioning media made from organic materials: husk charcoal, sawdust, and rice straw, and 2 (two) matriconditioning media made from inorganic materials: brick powder and fine sand. The results showed that the organic-based matriconditioning media group had a significant and better effect than the inorganic-based matriconditioning media on germination, germination speed, and germination uniformity, sprout dry weight, sprout length, number of leaves, and plant height of soybean. The treatment of organic matriconditioning media in the form of husk charcoal and sawdust has a better effect than other treatments.